2006
DOI: 10.1152/ajpheart.00353.2006
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin kinase II inhibition protects against myocardial cell apoptosis in vivo

Abstract: Inhibition of the multifunctional Ca(2+)/calmodulin-dependent protein kinase II (CaMKII) or depletion of sarcoplasmic reticulum (SR) Ca(2+) stores protects against apoptosis from excessive isoproterenol (Iso) stimulation in cultured ventricular myocytes, suggesting that CaMKII inhibition could be a novel approach to reducing cell death in conditions of increased adrenergic tone, such as myocardial infarction (MI), in vivo. We used mice with genetic myocardial CaMKII inhibition due to transgenic expression of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 45 publications
(64 reference statements)
4
115
0
1
Order By: Relevance
“…2+ load and promotes cardiomyocyte apoptosis induced by ISO treatment through the CaMKII pathway (31,32). Inhibition of CaMKII significantly decreased cardiomyocyte apoptosis induced by ISO in Pln-KO mice in vivo (31).…”
Section: Depletion Of Phd2/3 Results In Sustained Activation Of Camkimentioning
confidence: 99%
See 1 more Smart Citation
“…2+ load and promotes cardiomyocyte apoptosis induced by ISO treatment through the CaMKII pathway (31,32). Inhibition of CaMKII significantly decreased cardiomyocyte apoptosis induced by ISO in Pln-KO mice in vivo (31).…”
Section: Depletion Of Phd2/3 Results In Sustained Activation Of Camkimentioning
confidence: 99%
“…It has been documented that an increase in SERCA2a-to-PLN stoichiometry in cardiomyocytes leads to an increase in the SR Ca 2+ uptake rate (31). As expected, we demonstrated that the Ca 2+ uptake rate of crude heart homogenates from Phd2/3 fl/fl Cre +/-mice was sigprotein levels compared with combined depletion of PHD2 and PHD3 ( Figure 1C and Supplemental Figure 2C), suggesting that PHD2 is the major regulator of PLN in the heart and that PHD3 may play a compensatory role in the absence of PHD2.…”
Section: Depletionmentioning
confidence: 99%
“…CaMKII triggers sarcoplasmic reticulum Ca 2+ leak in heart failure (14), which may be an early contributor to membrane potential instability and arrhythmias. CaMKII is a proapoptotic signal during myocardial infarction (15), excessive catecholamine (16) and angiotensin II (8) exposure, and aortic banding surgery (17). Thus, CaMKII is a hypertrophic signaling molecule, but it participates in other cellular events that may be critical for the transition from early structural heart disease to heart failure and sudden death.…”
Section: Why Is Camkii Important In Myocardial Disease?mentioning
confidence: 99%
“…The identification of mutations in genes that are expressed by podocytes has explained the cause of a number of Mendelian glomerular diseases (8)(9)(10)(11)(12)(13) and has placed the podocyte in a central position in studies of glomerular disease. In patients with HIVAN, direct HIV-1 infection of podocytes has been documented, and viral proteins induce podocyte proliferation, loss of cell contact inhibition, and upregulation of growth factors in immortalized podocytes in culture (14)(15)(16)(17). The concept of a dysregulated podocyte phenotype in HIVAN has been proposed (15), and this phenotype is characterized by loss of expression of many genes typically seen in differentiated podocytes, such as synaptopodin (SYNPO), nephrosis 1 homolog (NPHS1; which encodes the slit-diaphragm protein nephrin), and NPHS2 (which encodes the podocyte slit diaphragm protein podocin), and with the re-expression of embryonic genes such as paired box gene 2 (PAX2) that are normally only expressed in presumptive podocytes and podocyte progenitors during glomerular development.…”
Section: Genetic Susceptibility To Hiv-associated Nephropathymentioning
confidence: 99%
“…The ␦ isoform of calcium/calmodulin (Ca 2ϩ /CaM)-dependent 3 protein kinase II (CaMKII␦) has emerged as a key mediator of a number of cellular functions in the heart, including ion channel regulation (1,2), gene transcription (3,4), and apoptotic cell death (5,6). CaMKII␦ is expressed as a homododecameric protein, and each monomer consists of three domains: a C-terminal association domain that directs multimeric assembly of the holoenzyme, an N-terminal catalytic domain that interacts with and phosphorylates substrates, and a regulatory domain that binds to the kinase domain and is autoinhibitory of CaMKII activity at baseline.…”
mentioning
confidence: 99%